Analysis of Moral and Religious Values of Early Childhood in the Animated Series "RIKO THE SERIES" - Fatmawati, Fitri Ayu (EDUTEC : Journal of Education And Technology, 2024)
The development of Religious and Moral Values is one of the aspects of development that must be developed in early childhood in terms of attitude and behaviour that can be stimulated by various media, one of which is television and gadgets. The purpose of this research is to find out the religious and moral messages contained in the animation show Riko The Series. This research uses library research method with qualitative research nature. The data collection technique used is documentation to find research data through scenes (film scripts, pictures, or films) from the animated cartoon Riko The Series. The results of this study indicate that the religious and moral values in the animated film Riko the Series are devoted to Allah SWT, grateful, love and ridho. Exemplifying the nature of the Prophet Muhammad, having a sincere soul, behaviour towards parents, other people or society.